Road Transport and their Impacts on Health - Ummul, Salma; K, Kameswara Rao (International Journal of Environment, Agriculture and Biotechnology, 2019)
Traffic contributes to a range of gaseous air pollutants and to suspended particulate matter (PM) of different sizes and composition. The effects on health of transport related air pollution are among the leading concerns. Research in recent decades consistently indicates the adverse effects of outdoor air pollution on human health.